2008
DOI: 10.1590/s0074-02762008000700011
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle, feeding and defecation patterns of Rhodnius ecuadoriensis (Lent & León 1958) (Hemiptera: Reduviidae: Triatominae) under laboratory conditions

Abstract: Rhodnius ecuadoriensis is the second most important vector of Chagas Disease (CD) in Ecuador. The objective of this study was to describe (and compare) the life cycle, the feeding and defecation patterns under laboratory conditions of two populations of this specie [from the provinces of Manabí (Coastal region) and Loja (Andean region)]. Egg-to-adult (n = 57) development took an average of 189.9 +/- 20 (Manabí) and 181.3 +/- 6.4 days (Loja). Mortality rates were high among Lojan nymphs. Pre-feeding time (from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…The average numbers of blood meals required for moulting to the next instar for T. protracta and T. rubida were similar to the values found for Rhodnius colombiensis (Mejia, Galvão, Jurberg), Rhodnius prolixus (Stål) and Rhodnius ecuadoriensis (Lent and León), whereas the average number of blood meals for T. recurva was higher than the average numbers for these three latter species (Arévalo et al 2007a, Villacís et al 2008). Because an increase in the number of vector-host interactions (for blood feeding) increases the probability of transmission of T. cruzi to hosts (Rocha et al 2001), the three currently studied species could be considered potentially epidemiologically important with respect to T. cruzi transmission to human populations.…”
Section: Discussionsupporting
confidence: 70%
“…The average numbers of blood meals required for moulting to the next instar for T. protracta and T. rubida were similar to the values found for Rhodnius colombiensis (Mejia, Galvão, Jurberg), Rhodnius prolixus (Stål) and Rhodnius ecuadoriensis (Lent and León), whereas the average number of blood meals for T. recurva was higher than the average numbers for these three latter species (Arévalo et al 2007a, Villacís et al 2008). Because an increase in the number of vector-host interactions (for blood feeding) increases the probability of transmission of T. cruzi to hosts (Rocha et al 2001), the three currently studied species could be considered potentially epidemiologically important with respect to T. cruzi transmission to human populations.…”
Section: Discussionsupporting
confidence: 70%
“…This level of mortality is similar to that obtained in B. ferroae fed on the vertebrate host in the present study (91%). In contrast, the two cohorts of B. ferroae fed on arthropods developed from the egg to adult stage with mortality rates of between 56-60%, which is similar to or even lower than the rates reported for other species of Triatominae fed on their natural vertebrate hosts (Bar et al 2003, Martínez-Ibarra et al 2003, 2007, Villacís et al 2008). …”
Section: Discussionsupporting
confidence: 48%
“…However, its capacity to transmit T. rangeli has not been evaluated yet. Recent studies have demonstrated that R. ecuadoriensis is an important threat for Chagas disease transmission due to its wide geographical distribution, high infection rates with T. cruzi, good vector efficiency, and capacity of adaptation to different habitats (Villacis et al 2008, Grijalva and Villacis 2009, SuarezDavalos et al 2010, Grijalva et al 2012, 2014. In this regard, the presence of R. ecuadoriensis, infected with T. rangeli, constitutes an important element to consider when the distribution of trypanosomes is evaluated in Chagas disease endemic areas.…”
Section: Discussionmentioning
confidence: 99%